(untitled) (Plant Bulletin, 2023)
The changing climate and continuously increasing global population has posed immense pressure on plant scientists to ensure per capita availability of food under scarcity of natural resources. The present circumstances also enforce to understand how rising CO2 level caused greenhouse effect in the environment which causes rise in the temperature and consequently influence the development of plant disease epidemic, to predict the genomic-based models under changing environmental conditions and to ensure continued food production. The application of genomics and bioinformatics tools are the innovative approaches to understand plant pathogen interaction and prediction that offers unique opportunities to enhance plant yield, stability in quality and production, boost the resilience of soybean to integrate resistance genes in present cultivars to sustain yield under epidemic disease conditions in abruptly changing climate. However, genomics data can be used for genomic based selections and advanced bioinformatics tools can be used to make predictions for genotype by pathogen interaction whereas it had ever been remained a great challenge to homogenize the diverse genomic data to which advanced skills and expertise are required in handling bioinformatics tools. Bioinformatics and genomics have the potential to sustain yield for food security by selection of tolerant or resistant genetic combination for disease sensitive environments as well as to facilitate for maintaining food security and mitigate the effect of inversely changing climatic conditions.